The empty plan : Film & Präsentation aus Depot & Archiven - Staatsgalerie, Stuttgart (2011)
In the series "Open Stores," the Staatsgalerie Stuttgart invites artists to work with its collection. The artists Anja Kirschner (b. 1977) and David Panos (b. 1971) from London will be presenting their "Open Stores" selection in correspondence with their new film "The Empty Plan," which was produced with support from the Staatsgalerie Stuttgart. The protagonist of the film-to be premiered in Germany within this framework-is the German author, dramatist and director Bertolt Brecht. In their selection of works, primarily from the store of the Staatsgalerie Stuttgart's Department of Prints, Drawings and Photographs, Kirschner and Panos explore the complex and ever-changing relationship between artistic forms and political movements in the critical period leading up to World War II.
Catalogue of an exhibition held at the Staatsgalerie Stuttgart, Germany, 29.06.2011 - 09.10.2011
Text in German and English.
boek